Shock reflection and surface effects in the shock tube - Busing, J. R.; Clarke, John F. (College of Aeronautics, 1966)
A thin-film resistance thermometer, mounted on the end-wall of a shock tube, is used to record surface temperatures and heat transfer rates following reflection of the primary shock wave. This information is combined with the results of theoretical investigations to produce simultaneous information about surface accommodation effects and gas thermal conductivities at high pressures and moderate temperatures.